2023
DOI: 10.1108/lodj-05-2023-0224
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inclusive leadership on innovative work behavior: a mediated moderation model

Abdullah Fahad AlMulhim,
Sanaa Mostafa Mohammed

Abstract: PurposeApplicable to telecom companies operating in Saudi Arabia, this study aims to investigate the mediating role of workplace dignity (WD) in the relationship between inclusive leadership and innovative work behavior (IWB) as well as the moderate role of workplace inclusion (WI) in said relationship.Design/methodology/approachA total of 364 telecom companies in Saudi Arabia participated in the survey study. SmartPLS was employed to evaluate the data and test the research variables.FindingsAccording to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…The study found that principal inclusive leadership independently predicted teacher innovative behavior, the stronger the principal inclusive leadership is, the more teacher innovative behaviors can be stimulated. This observation is consistent with previously published literature which demonstrated associations between inclusive leadership and innovative behaviors in Western 22 and Asian societies 57 .…”
Section: Discussionsupporting
confidence: 93%
“…The study found that principal inclusive leadership independently predicted teacher innovative behavior, the stronger the principal inclusive leadership is, the more teacher innovative behaviors can be stimulated. This observation is consistent with previously published literature which demonstrated associations between inclusive leadership and innovative behaviors in Western 22 and Asian societies 57 .…”
Section: Discussionsupporting
confidence: 93%
“…, 2022), change participation (Katsaros, 2022), learning from mistakes (Ye et al. , 2018) and innovative work behaviors (AlMulhim and Mohammed, 2023). Proactive behaviors are considered positive in the workplace, alongside the aforementioned behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study's findings provide additional support for the effectiveness of inclusive leadership in organizations. Inclusive leadership has been identified as a positive predictor of several behaviors, such as followers' work engagement (Bao et al, 2022), change participation (Katsaros, 2022), learning from mistakes (Ye et al, 2018) and innovative work behaviors (AlMulhim and Mohammed, 2023). Proactive behaviors are considered positive in the workplace, alongside the aforementioned behaviors.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The research results support hypothesis 1, which propounds that empathetic leadership promotes employees’ innovative behavior. The role of positive leadership in promoting innovative behavior has been discussed in the literature ( Iqbal et al, 2022 ; AlMulhim and Mohammed, 2023 ). Empathetic leadership, as a new type of positive leadership, mainly involves expressing empathy to employees, provides them with ways and means to obtain resources, and then promotes their innovative behavior.…”
Section: Discussionmentioning
confidence: 99%